APPLICATION OF GIS IN THE NATIONAL SECURITY AND DEFENSE SYSTEM OF UKRAINE - Humeniak, Roman; Ievsiukov, Taras; Slyusar, Yevhenii (SWorld-Ger Conference proceedings, 2025)
The role of geographic information systems (GIS) in ensuring the national security and defense of Ukraine in the conditions of armed aggression and digitalization of state administration is studied. The main directions of using GIS in the military sphere